Optimal reinforcing of reticular structures (2006)
This article presents an application of Genetic Algorithms (GA) and Finite Element Analysis (FEA) to the solution of a problem of structural optimization in plastic reticular structures. Structural optimization used to modify the original shape by placing reinforcements in optimal positions. As a result, a reduction in the maximum effort of 14.70% was obtained for a structure whose original volume increased by 8.36%. This procedure solves the problem of structural optimization by adjusting the original mold and avoiding the manufacture of a new mold.